Pengaruh Lagu terhadap Ketertarikan Siswa dalam Pembelajaran Kosakata Bahasa Arab - Nurfathonah, Lutfi Aji (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study focused on examining students' interest in memorizing Arabic vocabulary by using a song. The song has a variety of rhythmic sounds with the help of music that has been adjusted. Researchers studied 8th grade students at SMPIT ALFAWWAZ, by distributing questionnaires to students to be able to find out how much influence the song had on students' interest in memorizing Arabic vocabulary. The purpose of this study was to determine the effect of songs on learning on students' interest in memorizing Arabic vocabulary. This study uses a quantitative research method which will be tested using SPSS 26 software with the results being tested by various tests such as the normality test, simple linear regression analysis and the coefficient of determination test. The results of the study which were tested on 38 students found that songs in learning influenced students' interest in memorizing Arabic vocabulary. Through the results of the coefficient of determination test, it was found that the x variable affects the y variable by 11.8% of the results of the variables that have been tested.